Perbandingan Lembaga Pemberantasan Narkotika: BNN (Indonesia) dan PDEA (Filipina) dalam Pilar Regulatif dan Normatif - Shahla Eliza Nurhidayah; Hauralya Salsabilla; Anggita Puspa Nirwana; Denissa Angela Sihombing; Rudiana Rudiana (Pusat Riset dan Inovasi Nasional, 2025)
This research compares the institutional frameworks of Indonesia’s National Narcotics Agency (BNN) and the Philippine Drug Enforcement Agency (PDEA) through the lens of regulatory and normative pillars from W. Richard Scott’s institutional theory. Employing a qualitative descriptive method with a literature review approach, this study finds that both agencies are structurally under presidential authority but exhibit differing operational styles. BNN emphasizes preventive and rehabilitative strategies rooted in human rights values, while PDEA is characterized by a more repressive approach shaped by national security paradigms. The findings suggest that while both institutions have formal legitimacy and enforcement mechanisms, their normative orientations differ significantly, influencing public perception, legitimacy, and policy outcomes. This comparative study highlights the importance of aligning regulatory frameworks with ethical governance standards to ensure effective and humane narcotics control policies.